Opioid substitution therapy clients' preferences for targeted versus general primary health‐care outlets. (27th August 2012) - Islam, M. Mofizul; Topp, Libby; Conigrave, Katherine M.; Day, Carolyn A.
Abstract Introduction and Aims. Opioid substitution therapy (OST) ideally constitutes a window of opportunity for the provision of essential primary health care (PHC) for OST clients. In the absence of such opportunities, however, OST clients access PHC from existing outlets, either general services or those targeted to specific groups. This study examined OST clients' current main source and preferred future outlets of PHC services and correlates of preferences. Design and Methods. Anonymous interviews conducted with n = 257 clients of two public OST clinics in Sydney's inner‐west. Results. Overall, 61% (n = 158) of participants reported currently accessing PHC primarily from general outlets (general practitioners or medical centres: 51%, hospital/emergence departments: 10%) and the remainder (39%, n = 99) from outlets that target specific groups (e.g. Aboriginal Medical Services, OST prescriber/clinics, drug user‐targeted PHCs). Twenty‐two percent reported discomfort disclosing drug use to their current PHC providers. However, the majority were satisfied with the care they received and reported a preference to remain with their current PHC providers for a range of reasons, most commonly familiarity with and trust in staff (56%) and not feeling judged about their drug use (49%). Nevertheless, 28% reported that they would access PHC through their OST clinic if it were available. Discussion and Conclusions. PHC outlets that target specific groups appear to have an ongoing and important role in providing accessible health care to OST clients.